Breaking Bad Behaviors: A New Tool for Learning Classroom Management Using Virtual Reality - Lugrin, Jean-Luc; Latoschik, Marc Erich; Habel, Michael; Roth, Daniel; Seufert, Christian; Grafe, Silke (Frontiers in ICT, 2016)
This article presents an immersive Virtual Reality (VR) system for training classroom management skills, with a specific focus on learning to manage disruptive student behaviour in face-to-face, one-to-many teaching scenarios. The core of the system is a real-time 3D virtual simulation of a classroom, populated by twenty-four semi-autonomous virtual students. The system has been designed as a companion tool for classroom management seminars in a syllabus for primary and secondary school teachers. Whereby, it will allow lecturers to link theory with practice, using the medium of VR. The system is therefore designed for two users: a trainee teacher and an instructor supervising the training session. The teacher is immersed in a real-time 3D simulation of a classroom by means of a head-mounted display and headphone. The instructor operates a graphical desktop console which renders a view of the class and the teacher, whose avatar movements are captured by a marker-less tracking system. This console includes a 2D graphics menu with convenient behaviour and feedback control mechanisms to provide human-guided training sessions. The system is built using low-cost consumer hardware and software. Its architecture and technical design are described in detail. A first evaluation confirms its conformance to critical usability requirements (i.e., safety and comfort, believability, simplicity, acceptability, extensibility, affordability and mobility). Our initial results are promising, and constitute the necessary first step toward a possible investigation of the efficiency and effectiveness of such a system in terms of learning outcomes and experience.